Factors associated with difficulty in hospital acceptance during the COVID-19 pandemic period in Osaka Prefecture, Japan: a population-based study - Katayama, Yusuke; Tanaka, Kenta; Nakao, Shunichiro; Tachino, Jotaro; Hirose, Tomoya; Dohmi, Hisaya; Kitamura, Tetsuhisa; Oda, Jun; Matsuoka, Tetsuya (Frontiers in Public Health, 2024)
Background In many countries, emergency medical systems were responsible for initial treatment of patients with COVID-19. Generally, acceptance by medical institutions may not be sufficient, and it may take much time to determine the medical institution to which to transport the patient. This problem is termed “difficulty in hospital acceptance (DIH),” and it is used as a key performance indicator in the assessment of the EMS in Japan. The purpose of this study was to reveal the factors associated with the DIH during the COVID-19 pandemic using dataset in the ORION (Osaka emergency information Research Intelligent Operation Network system). Methods This was a retrospective descriptive study with a 3-year study period from January 1, 2019 to December 31, 2021. We included patients who were recorded in the ORION system during the study period. The primary endpoint was defined as DIH. Multivariable logistic regression model was used to assess factors associated with DIH during the COVID-19 pandemic and calculated their adjusted odds ratio (AOR) and associated 95% confidence interval (CI). Results 1,078,850 patients included in this study. Of them, 41,140 patients (3.8%) experienced DIH and 1,037,710 patients (96.2%) did not experience DIH. The median age was 71 years (IQR: 45–82), and 543,760 patients (50.4%) were male. In this study, SpO2, body temperature, and epidemic period of COVID-19 were associated with difficulty in hospital acceptance. The highest AOR of SpO2 was 80% or less (AOR: 1.636, [95% CI: 1.532–1.748]), followed by 81–85% (AOR: 1.584, [95% CI: 1.459–1.721]). The highest AOR of body temperature was 38.0–38.9°C (AOR: 1.969 [95% CI: 1.897–2.043]), followed by 39°C or higher (AOR: 1.912 [95% CI: 1.829–1.998]). The highest AOR of epidemic period of COVID-19 was the 4th wave (AOR: 2.134, [95% CI: 2.065–2.205]), followed by the 3rd wave (AOR: 1.842, [95% CI: 1.785–1.901]). Conclusion In this study, we revealed factors associated with the DIH during the COVID-19 pandemic. As various factors are involved in the spread of an unknown infectious disease, it is necessary not only to plan in advance but also to take appropriate measures according to the situation in order to smoothly accept emergency patients.